Integration of Religious Values in Cultural Education to Improve the Character of the Young Generation - Adhitama, Satria; Fajrin, Fajrin (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Character education is the main foundation in the formation of human resources with integrity amidst the challenges of globalization and the moral crisis of the younger generation. This article examines how the integration of religious values ​​in cultural education can be an effective strategy to strengthen the character of the younger generation of Indonesia. This research was conducted through a qualitative approach based on literature studies from 10 relevant national and international scientific articles. The findings show that the integration of religious values ​​and local culture can create a deep educational ecosystem, not only in the cognitive aspect, but also touching the affective and spiritual realms of students. In a formal environment, these values ​​are integrated through the curriculum, school culture, and contextual learning methods based on local wisdom. Meanwhile, in a non-formal environment, teaching practices based on religious communities, Islamic boarding schools, and madrasas play an important role in the formation of students' social and spiritual character. This article also highlights the importance of role models and environmental consistency in making religious and cultural values ​​an integral part of students' lives. The results of this study recommend a character education model that is integrated with the nation's cultural and religious identity as a holistic approach in responding to the moral challenges of the younger generation, while supporting the vision of Indonesia Emas 2045.